THE EFFECT OF GEOGEBRA-ASSISTED DISCOVERY LEARNING ON MATHEMATICAL CONCEPT UNDERSTANDING IN STATISTICS LEARNING - Masroh Saragih; Elfira Rahmadani (Universitas Muhammadiyah Metro, 2026)
This study aims to determine the effect of the Discovery Learning model assisted by GeoGebra on students' mathematical conceptual understanding ability in Statistics (Measures of Central Tendency) for Grade X students at SMA Negeri 1 Air Joman in the 2025/2026 Academic Year. This research employed a quantitative approach using a quasi-experimental method with a Pretest-Posttest Control Group Design. The population consisted of all Grade X students, comprising 6 classes with a total of 206 students. The samples were Class X-2 as the experimental class and Class X-4 as the control class. After the learning process was completed, the posttest results showed that the experimental class achieved higher scores than the control class. Therefore, it can be concluded that students' mathematical conceptual understanding taught through the Discovery Learning model assisted by the GeoGebra application is better than that of students taught through the direct instruction model. Penelitian ini bertujuan untuk mengetahui pengaruh model discovery learning berbantuan geogebra terhadap kemampuan pemahaman konsep matematis siswa pada materi Statistika (Ukuran Pemusatan Data) Kelas X SMA Negeri 1 Air Joman Tahun Ajaran 2025/2026. Jenis penelitian ini adalah penelitian kuantitatif, menggunakan metode penelitian quasy experiment dengan desain penelitian adalah Pretest-Posttest Control Group Design. Populasi pada penelitian ini seluruh siswa kelas X yang berjumlah 6 kelas sebanyak 206 siswa. Sampel yang diambil kelas X-2 sebagai kelas eksperimen dan kelas X-4 sebagai kelas kontrol. Setelah proses pembelajaran selesai dilaksanakan, diperoleh hasil posttest kelas eksperimen lebih tinggi dibanding kelas kontrol. Dengan demikian diperoleh kesimpulan bahwa kemampuan pemahaman konsep matematis siswa menggunakan model Discovery Learning berbantuan Aplikasi Geogebra lebih baik dibandingkan menggunakan model pembelajaran langsung.